1999
DOI: 10.1177/009127009903900505
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Z‐321, a Novel Specific Orally Active Prolyl Endopeptidase Inhibitor, in Healthy Male Volunteers

Abstract: This study investigates the pharmacokinetics and safety profile of Z‐321, (4R)‐3‐(indan‐2‐ylacetyl)‐4‐(1‐pyrrolidinylcarbonyl)‐1,3‐thiazolidine, a novel specific orally active prolyl endopeptidase (PEP) inhibitor. Following a preliminary safety evaluation wherein 2 subjects received 3.75 and 15 mg doses and 2 other subjects received 7.5 and 30 mg doses, 16 subjects were assigned to two groups of 8 subjects each. In each group, 6 subjects were to receive active treatment, and 1 or 2 subjects were to receive pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Prolyl oligopeptidase inhibition produced disease-modifying effects by activating PP2A, consequently reducing tau phosphorylation, enhancing autophagy, and reducing oxidative stress; thus, i.e., it provided a multitarget approach to tackle tau-dependent toxicity in the PS19 mice. Furthermore, neither toxicity nor serious adverse events have been reported in previous preclinical or clinical studies after prolyl oligopeptidase inhibition ( 75 77 ). Prolyl oligopeptidase inhibition could have potential as a disease-modifying treatment for tauopathies and maybe other neurodegenerative diseases characterized by multiple toxic mechanisms ( 78 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Prolyl oligopeptidase inhibition produced disease-modifying effects by activating PP2A, consequently reducing tau phosphorylation, enhancing autophagy, and reducing oxidative stress; thus, i.e., it provided a multitarget approach to tackle tau-dependent toxicity in the PS19 mice. Furthermore, neither toxicity nor serious adverse events have been reported in previous preclinical or clinical studies after prolyl oligopeptidase inhibition ( 75 77 ). Prolyl oligopeptidase inhibition could have potential as a disease-modifying treatment for tauopathies and maybe other neurodegenerative diseases characterized by multiple toxic mechanisms ( 78 ).…”
Section: Discussionmentioning
confidence: 97%
“…Prolyl oligopeptidase inhibition produced disease-modifying effects by activating PP2A, consequently reducing tau phosphorylation, enhancing autophagy, and reducing oxidative stress; thus, i.e., it provided a multitarget approach to tackle tau-dependent toxicity in the PS19 mice. Furthermore, neither toxicity nor serious adverse events have been reported in previous preclinical or clinical studies after prolyl oligopeptidase inhibition (75)(76)(77) A priori power analysis based on our behavioral characterization experiments was performed for the sample size estimation of PS19 transgenic mice needed in the treatment phase of the in vivo study. With an α = 0.05 and power (1 -β) = 0.9, the estimated sample size for four treatment groups was 71 to achieve a 0.5 effect size between the treatment groups (G*power, version 3.1.9.2.).…”
Section: Discussionmentioning
confidence: 99%
“…The crude product was obtained as a yellow sap, which after flash chromatography (heptane/ EtOAc 17:3 → 1:4) yielded compound 15 as a yellow oil (87 mg, 20%). 1 (16). Synthesized according to method A using compound 47 (854 mg, 2.47 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…The development of PREP ligands was originally focused on inhibiting proteolytic activity, and a few potent inhibitors entered clinical trials. These trials did not advance, to our understanding, due to a lack of efficacy, but they showed that at least short-term PREP inhibition is safe in humans. Interestingly, the most recent compound that entered clinical trials, S17092, had no effect on the PPI-mediated functions of PREP when it was later evaluated in our assays .…”
Section: Introductionmentioning
confidence: 99%